Ergonomic evaluation and optimization of levels of temperature, viewing angle and viewing distance on text readability task / Zulquernain Mallick, Abid Haleem and Arshad Noor Siddiquee (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2008)
The widespread usage of computers and its prolonged use has been shown to be a risk factor for musculoskeletal and visual discomfort. This paper presents a study in which the effect of operating parameters such as levels of temperature, viewing angle and viewing distance were analyzed. In addition, the Taguchi method, a powerful tool to design and process optimization for quality, is used to find the optimal parameters for the text reading task in order to get a minimum level of visual discomfort and improved performance (from a readability point of view). The orthogonal array, the signal-to-noise (S/N) ratio and the analysis of variance (ANOVA) were employed to obtain optimum combination of process parameters and their levels. Results show that the combination of parameters in which temperature at level 2 (27°C), viewing angle at level I (15°) and the viewing distance at level 2 (60 cm) produces maximum efficiency from readability point of view. It has also been found that the temperature level is the dominant parameter with a maximum percentage contribution of 75.74% followed by the viewing angle 4.23% and viewing distance 3.12%.